Diaqua(1,4,8,11-tetraazacyclotetradecane-kappa4 N1,N4,N8,N11)copper(II) bis(2,3,4,5,6-pentafluorobenzoate) dihydrate - Tan, Kong Wai; Ng, S.W.; Tajidi, N.S.A.; Abdullah, N.; Arifin, Z. (International Union of Crystallography, 2010)
The CuII atom in the title salt, [Cu(C(10)H(24)N(4))(H(2)O)(2)](C(6)F(5)CO(2))(2)center dot 2H(2)O, is chelated by the four N atoms of the 1,4,8,11-tetraazacyclotetradecane (cyclam) ligand and is coordinated by two water molecules in a Jahn-Teller-type tetragonally distorted octahedral geometry. The CuII atom lies on a center of inversion. The cations, anions and uncoordinated water molecules are linked by N-H...O and O-H...O hydrogen bonds, forming a layer structure parallel to (001).